Therapeutic Potential of TNFα and IL1β Blockade for CRS/ICANS in CAR-T Therapy via Ameliorating Endothelial Activation - Chen, Yunshuo; Li, Ranran; Shang, Siqi; Yang, Xuejiao; Li, Lei; Wang, Wenbo; Wang, Yueying (Frontiers in Immunology, 2021)
Severe cytokine release syndrome (CRS) and neurotoxicity associated with chimeric antigen receptor T cell (CAR-T) therapy strongly hampered the broad clinical applicability of this treatment. Vascular endothelial activation has been suggested to contribute to the development of CRS and neurotoxicity after CAR-T therapy. However, till now, therapeutic strategies targeting endothelial dysfunction during CAR-T therapy have not been studied yet. Here, we found that tumor necrosis factor ⍺ (TNF⍺) produced by CAR-T cells upon tumor recognition and interleukin 1β (IL1β) secreted by activated myeloid cells were the main cytokines in inducing endothelial activation. Therefore, we investigated the potential effectiveness of TNF⍺ and IL1β signaling blockade on endothelial activation in CAR-T therapy. The blockade of TNF⍺ and IL1β signaling with adalimumab and anti-IL1β antibody respectively, as well as the application of focal adhesion kinase (FAK) inhibitor PF-562271, effectively ameliorated endothelial activation induced by CAR-T, tumor cells, and myeloid cells. Moreover, adalimumab and anti-IL1β antibody exerted synergistic effect on the prevention of endothelial activation induced by CAR-T, tumor cells, and myeloid cells. Our results indicate that TNF⍺ and IL1β blockade might have therapeutic potential for the treatment of CAR-T therapy-associated CRS and neurotoxicity.